Women and Pensions in Italy: Gender Imbalances and the Equalization of Retirement Age - De Luigi, Nicola; Rizza, Roberto; Santangelo, Federica (Frontiers in Sociology, 2021)
This paper examines the age at retirement for men and women in Italy. Despite the expansion of women’s educational attainments, they still display lower employment rates, are frequently engaged in involuntary part-time jobs and have more fragmented careers. As a consequence, the mean age at which women receive a pension is higher than that of men. Using Labour Force Survey (2006 and 2012), the authors test the hypothesis that women’s higher age at retirement is determined by a selection bias towards more educated and work oriented women. A Heckman selection model has been developed. Results show that the main disadvantage is suffered by women with medium and low levels of education who show the highest estimated age at retirement, whereas higher educated women retire on average before men with the same level of education. The authors argue that pension policies, without interventions in the field of work-life balance policies, end up penalizing women with lower levels of education.